The Strained Relation Between Samaritans and Jews in the Works of Flavius Josephus - Albertus Purnomo (STF Driyarkara - Diskursus, 2017)
Abstract: The strained relation between Samaritans and Jews as a fruit of long-term process from the division of the United Kingdom of Israel (ca. 931 B.C.E) became a dominant issue since the post-exilic period and became more pronounced in the first century C.E. Beside the Old Testament, the story of their relation which was full of conflict can be traced to extra-biblical sources. One of them is Flavius Josephus works (ca. 70 to 100 C.E), i.e., Jewish War and Jewish Antiquities. The root of the conflict is related to the presence of the Second Jerusalem Temple. The peak of the conflict is the construction of the Mount Gerizim temple in which some Jews regarded the adherents of the Samaritan cult as schismatic. The founding of this rival temple of Jerusalem aggravated the bad relations between Samaritans and Jews. The destruction of the Mount Gerizim temple by John Hyrcanus was a crucial incident for their relations. The conflict between Samaritans and Jews still continued in the Roman period. By historical approach, this study would setforth the examination of some Josephus accounts regarding the historical process of the estrangement and rivalry between Samaritans and Jews which resulted in the final split in second century B.C.E. Keywords: Samaritans, Jews, Flavius Josephus, Jewish Antiquities, Temple, Jerusalem, Mount Gerizim. Abstrak: Relasi tegang antara orang Samaria dan Yahudi merupakan buah dari proses yang panjang sejak pecahnya Kerajaan Israel Raya (sekitar 931 B.C.E). Relasi mereka ini menjadi masalah dominan sejak periode setelah pembuangan dan semakin jelas pada abad pertama masehi. Di samping Perjanjian Lama, kisah tentang relasi mereka yang penuh konflik dapat dilacak dalam sumber-sumber di luar Alkitab. Salah satunya adalah karya dari Flavius Josephus (sekitar 70 sampai 100 M), yaitu Perang Yahudi dan Sejarah Yahudi. Akar dari konflik itu adalah kehadiran Bait Allah Yerusalem Kedua. Puncak dari konflik itu adalah pembangunan Bait Allah di Gunung Gerizim di mana sejumlah orang Yahudi kemudian menganggap pengikut ibadah orang Samaria sebagai skismatis. Pendirian tandingan Bait Allah Yerusalem ini memperparah relasi buruk antara Samaria dan Yahudi. Penghancuran Bait Allah di Gunung Gerizim oleh Yohanes Hyrcanus menjadi insiden krusial bagi relasi mereka. Konflik antara orang Samaria dan Yahudi masih terus berlangsung pada periode Romawi. Dengan pendekatan historis, studi ini akan memaparkan penelitian kisah-kisah dari karya Josephus berkaitan dengan proses perpecahan dan persaingan antara orang Samaria dan Yahudi memuncak pada perpecahannya pada abad II SM. Kata-kata Kunci: Samaria, Yahudi, Flavius Josephus, Sejarah Yahudi, Bait Allah, Yerusalem, Gunung Gerizim.